Neil DNA glycosylases promote substrate turnover by Tdg during DNA demethylation - Schomacher, Lars; Han, Dandan; Musheev, Michael U.; Arab, Khelifa; Kienhöfer, Sabine; Seggern, Annika von; Niehrs, Christof (Nature structural & molecular biology, 2016)
During oxidative DNA demethylation, Neil DNA glycosylases stimulate processing of abasic sites generated by Tdg, which excises 5-methylcytosine oxidation products generated by Tet dioxygenases, promoting restoration of unmodified cytosines via base excision repair.